#### Answer

a) $-6$ and $7$
b) $a_{n+1} = |a_n + 1| * (-1)^n$, $a_1 = 1$
c) $a_n = (-1)^{n+1} n$

#### Work Step by Step

a) The absolute value of the number is increasing, with the terms alternating in signs. Thus, the next two terms would be $-6$ and $7$
b) Since the first term is 1, $a_1 = 1$.
The absolute value increases by one every iteration and it alternates signs, starting with positive.
$a_{n+1} = |a_n + 1| * (-1)^n$
c) The $n$ reflects the absolute value, and the sign is even whenever the $n$ is odd.
Thus, the formula would be:
$a_n = (-1)^{n+1} n$